Wirkungen der Beschäftigungspflicht schwerbehinderter Arbeitnehmer: Erkenntnisse aus der Einführung des "Gesetzes zur Bekämpfung der Arbeitslosigkeit Schwerbehinderter" - Nils Braakmann (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– This paper uses new administrative data from the German Federal Employment Agency - the Integrated Employment Biographies Sample IEBS - to assess the impact of a mandatory employment quota for disabled workers in Germany. We use an exogenous change, introduced through the 'Law to Combat Unemployment among Severely Disabled People' ('Gesetz zur Bekämpfung der Arbeitslosigkeit Schwerbehinderter'), as a natural experiment and measure the change in the reemployment probability of the unemployed disabled by means of regression-adjusted difference-indifferences estimators. Our results indicate that the change in the employment quota neither enhanced nor worsened the employment prospects of the disabled.
Keywords: 330; Schwerbehinderte; Erwerbsquote; Arbeitslose; Integrierte Erwerbsbiografien; Arbeitnehmer; Personaleinstellung; Arbeitslosigkeitsbekämpfung; Gesetzgebung; Beschäftigungseffekte; Behindertenpolitik - Auswirkungen; Behindertenrecht; Arbeitsmarktchancen; Personalpolitik; Unternehmen; Betrieb